Analisis Kesulitan Belajar Siswa pada Materi Fungsi Trigonometri di Kelas XI SMA Negeri 2 Baubau - Anwar Anwar; Ernawati Jais; La Eru Ugi; Windi A. Balani (Jurnal Akademik Pendidikan Matematika, 2026)
The problem statement of this study is, what are the learning difficulties of grade XI students of SMA Negeri 2 Baubau in solving trigonometry problems?This study aims to determine the learning difficulties of grade XI students of SMA Negeri 2 Baubau in solving trigonometry problems. This study used a qualitative method with a descriptive method. The subjects were 34 grade XI.9 students of SMA Negeri 2 Baubau. The instruments are tests and interview guidelines. These intsrumens are used to obtain data on the learning difficulties experienced by students and the factors contributing to these difficulties. After the data were collected by using tests and interviews, than they were analyzed by using data reduction, data presentation, and conclusion drawing. Based on the research results, the conclusion of this research shows that students experience difficulties in four indicators: (1) difficulty in determining the steps for solving problems, (2) understanding concepts or formulas, (3) stating relationships between problem components, and (4) performing mathematical operations. The cause of these difficulties came from internal factors, such as a lack of conceptual understanding and limited cognitive abilities, as well as external factors such as a lack of active participation in learning and the teacher’s delivery methods.